Induction of macrophage procoagulant activity by Bacteroides fragilis. - Rosenthal, G A (1989)
Fibrin deposition in the peritoneal cavity during acute peritonitis appears to predispose the host to abscess formation by providing an environment for bacterial proliferation protected from host defenses. The purpose of the present study was to determine whether the potent abscess-inducing anaerobe Bacteroides fragilis could promote fibrin deposition by inducing mononuclear cells to express procoagulant activity (PCA). B. fragilis stimulated PCA in a dose-dependent fashion, achieving a maximum at 10(7) CFU/ml. Heat-killed B. fragilis induced comparable levels of PCA, while a nonspecific phagocytic stimulus, latex beads, was not stimulatory. B. fragilis was capable of inducing PCA even when phagocytosis was blocked by preexposure of cells to latex beads. The results suggested that phagocytosis was neither necessary nor sufficient for the generation of PCA. Cell separation studies showed that PCA was solely produced by macrophages and that lymphocytes did not augment its production. These studies suggest one potential mechanism by which B. fragilis might initiate abscess formation.